Pengembangan Repositori Data Primer Riset Nasional: Studi Kasus Badan Riset dan Inovasi Nasional - Suminarsih, Eka Meifrina; Afandi, Sjaeful (Jurnal IPI (Ikatan Pustakawan Indonesia), 2023)
The spread of various repositories in institutions of Indonesia of course does not make it easy for data owners and data users to access data that has been stored in various repositories. In addition, different types of data, metadata and software used in storing research data are also a problem in the process of accessing all data in each institution. Therefore we need a national scientific repository that integrates all scientific data scattered, namely the National Scientifc Repository (NSR). NSR has been developed by BRIN. It is necessary to make observation about RIN to find out contribution of RIN in preserving research in Indonesia. The method in this research is a qualitative descriptive research. The result that RIN BRIN has roles in the process of collecting, processing, storing and accessing research primary data. RIN BRIN also facilitates data exchange and dissemination of research results so that it can support government program in one data in Indonesia. The development of RIN BRIN continues to be carried out so that data is maintained, safe and accessible according to developments in information technology.